Tetraphenylethene (TPE) modified polyhedral oligomeric silsesquioxanes (POSS): unadulterated monomer emission, aggregation-induced emission and nanostructural self-assembly modulated by the flexible spacer between POSS and TPE. Issue 84 (3rd October 2016) - Zhou, Hui; Li, Jiesheng; Chua, Ming Hui; Yan, Hong; Ye, Qun; Song, Jing; Lin, Ting Ting; Tang, Ben Zhong; Xu, Jianwei
Abstract : Mono-TPE modified POSS molecules exhibit monomer and AIE emission under different conditions. Abstract : Mono-TPE modified POSS molecules, in which the flexible spacers between TPE and POSS moieties control their self-assembly and aggregation, exhibit a unique unadulterated monomer emission in organic solvents as well as an AIE emission in THF/water.